2022
DOI: 10.3390/ijerph19031075
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Occupational Stress among Office Workers—A Focus Group Study

Abstract: Workplace stress remains a major interest of occupational health research, usually based on theoretical models and quantitative large-scale studies. Office workers are especially exposed to stressors such as high workload and time pressure. The aim of this qualitative research was to follow a phenomenological approach to identify work stressors as they are perceived by office workers. Six focus groups with office workers of different occupations were conducted in Belgium and Slovenia. A total of 39 participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
3
17
0
Order By: Relevance
“…It is this imbalance of roles that allows academic procrastination to occur. This is in accordance with research conducted by Bolliger et al, (2022), Kurniawan and Rahayu (2022) and Mardelina and Muhson (2017). With a high workload, it will trigger conflicts in the imbalance of roles as student.…”
Section: E Relationship Of Workload On Work School Conflictsupporting
confidence: 89%
See 1 more Smart Citation
“…It is this imbalance of roles that allows academic procrastination to occur. This is in accordance with research conducted by Bolliger et al, (2022), Kurniawan and Rahayu (2022) and Mardelina and Muhson (2017). With a high workload, it will trigger conflicts in the imbalance of roles as student.…”
Section: E Relationship Of Workload On Work School Conflictsupporting
confidence: 89%
“…Academic procrastination is a deliberate delay to start completing academic tasks that are carried out repeatedly by preferring to carry out other activities that do not need to be done and will usually be done close to the dateline of the task collection limit (Solomon & Rothblum, 1984, as cited in Abriliah, 2022. Work that does not look at the working hours and workload of each employee causes the employee to only have time to focus on their work and not meet their demands or obligations in lectures, with this imbalance of activities allowing them to procrastinate the academy This is in accordance with research conducted by Bolliger et al, (2022) and Dinata & Supriyadi (2019) which found that workload has a positive influence on academic procrastination.…”
Section: A Relationship Of Workload On Academic Procrastinationsupporting
confidence: 82%
“…The participating office workers reported that decision latitude—a subscale of job control of the Job Demand-Control-Support model (Karasek et al 1998 )—was of high relevance to them in their work experiences, providing freedom and the liberty to make their own decisions. However, it was also reported to be very stressful when work limits were not set (Bolliger et al 2022 ). A second focus group study confirmed that high responsibility can result in self-doubt, insecurity, or even burnout (Ironside et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Workers in the manufacturing industry become stressed as a result of high job expectations, lengthy and irregular working hours, and tough work shift patterns in order to reach production objectives and maintain customer satisfaction. Constant work stress and pressure result in both physical and mental exhaustion, a lack of work-life balance, and decreased employee productivity ( Bhui et al, 2016 ; Bolliger et al, 2022 ; Kim and Jung, 2022 ). Hopelessness, not feeling useful, and feeling depressed in the work environment are considered factors associated with symptoms of work-related stress among factory workers ( Sznajder et al, 2022 ), highlighting the need for interventions to alleviate poor mental health symptoms among workers in high-pressure occupational environments.…”
Section: Introductionmentioning
confidence: 99%